Pemberdayaan Perempuan Pesisir Sebagai Poros Utama Pembangunan Berkelanjutan di Desa Kapetakan Kabupaten Cirebon: Membangun Kesetaraan, Kesejahteraan, dan Keseimbangan Lingkungan - Rexy Nakula Urbaningrum (Syntax Corporation Indonesia, 2025)
This study aims to explore the dynamics of coastal women's empowerment in Kapetakan Village, Cirebon Regency, using a qualitative observational approach. In the context of coastal women’s empowerment, it is often overlooked that the potential of local women in managing natural resources sustainably can have a significant impact on both economic and social aspects. This research focuses on the factors that influence the empowerment of coastal women, including their skills, access to resources, and involvement in community decision-making. Through direct observation, in-depth interviews, and documentation, the findings reveal that women's empowerment in this village is driven by initiatives based on local wisdom and collaboration with local community groups as well as the government. Nevertheless, challenges related to patriarchal cultural patterns and limited access to education and technology remain the main obstacles. This study proposes the importance of the involvement of both government and non-governmental organizations to address these challenges through more inclusive programs.